A method for preparing low-grade high-iron fly ash-based hierarchical pore A-type molecular sieve without a template agent and application of the same in adsorbing low-concentration carbon dioxide
Patent Information
- Application Number
- CN202610307554.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-03-13
AI Technical Summary
[0004]然而,目前的粉煤灰基分子筛方案仍存在一些不足之处:(1)当粉煤灰中的铁含量过高时,通过预处理工艺很难将其中高含量的铁元素去除至合理范畴,对于预处理过程中铁的变化情况,以及铁元素对粉煤灰合成分子筛的影响没有系统的研究
本发明通过独特的预处理与合成工艺,将高铁粉煤灰中的杂质铁部分转化为有益组分,并同步构建多级孔结构,最终制备出对于低浓度CO2具有优异吸附性能的分子筛吸附剂。该方法实现了铁物种从原料中的氧化物形态,向最终产物中的骨架掺杂形态(Fe-O-Si)的可控转变。这一过程不仅避免了铁对结晶过程的负面影响,反而使其成为提升吸附性能的活性位点。在不引入造孔剂的情况下,利用本发明限定的制备工艺可以调控晶体生长与聚集行为,原位制得多级孔结构,并且该分子筛对于低浓度CO2的吸附容量高,可用于烟道气中CO2的捕集,有很好的应用价值。本发明的制备方法简单、方便,仅涉及常规化工设备,能耗与原料成本低,具备大规模工业生产的潜力。
Smart Images

Figure CN122032522B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of molecular sieves, and in particular to a method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without template agents and their application in adsorbing low concentrations of carbon dioxide. Background Technology
[0002] Molecular sieves, with their unique structural characteristics, possess properties such as ion exchange, adsorption, and catalysis. However, the cost of preparing molecular sieves using analytical grade reagents is high, making large-scale production difficult. Therefore, finding widely available and inexpensive raw materials as alternatives is an important research direction. Fly ash, with its chemical composition similar to that of molecular sieves, is considered a promising low-cost raw material. Synthesizing molecular sieves using fly ash can not only promote the high-value utilization of solid waste resources but also alleviate environmental pressure, offering both good ecological and economic benefits.
[0003] In recent years, molecular sieves, as a relatively mature adsorption material, have shown promising application prospects in the field of CO2 capture. Molecular sieves possess abundant pore structures; for example, type A molecular sieves have a theoretical pore size of 0.3-0.5 nm, which is larger than the critical diameter of CO2 molecules (0.28 nm), thus demonstrating the physical feasibility of adsorbing CO2. Existing research has confirmed that type X or NaX molecular sieves can be synthesized using fly ash and used for CO2 adsorption.
[0004] However, current fly ash-based molecular sieve schemes still have some shortcomings: (1) When the iron content in fly ash is too high, it is difficult to remove the high iron content to a reasonable range through pretreatment processes. There is no systematic study on the changes in iron during pretreatment and the influence of iron on the synthesis of molecular sieves from fly ash. (2) For fly ash with high iron content, existing methods for synthesizing single-configuration molecular sieves mostly rely on template agents, microwave assistance, and ultrasonic assistance. However, there are few studies on the direct synthesis of single-configuration and well-crystallized molecular sieves through a simple hydrothermal method without template agents. (3) For the adsorption of low-concentration CO2 waste gas such as flue gas from coal-fired power plants, existing fly ash-based molecular sieves have poor adsorption effects, and there is a lack of research on the optimization of relevant adsorption process parameters and adsorption kinetics. Therefore, how to develop a method that can directly and efficiently utilize high-iron fly ash, avoid the use of complex template agents, and thus prepare molecular sieve materials with excellent adsorption performance for low-concentration CO2 has important technical significance and economic value. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without template agents and its application in adsorbing low-concentration carbon dioxide, so as to solve the above-mentioned problems in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without a template agent, comprising the following steps: Low-grade high-iron fly ash is calcined, acid-washed, and activated by alkali fusion to obtain pretreated fly ash, which is then subjected to a crystallization reaction to complete the preparation. The low-grade high-iron fly ash has an Fe2O3 mass fraction of 20-40%.
[0007] Preferably, the calcination temperature is 750°C and the time is 2 hours.
[0008] Preferably, the pickling solution is a hydrochloric acid aqueous solution with a concentration of 6-7 mol / L.
[0009] Preferably, the pickling temperature is 90~95℃ and the time is 5-6 hours.
[0010] Preferably, the alkali fusion activation includes the following steps: mixing sodium carbonate and acid-washed fly ash at a mass ratio of 1.2:1, and then calcining at 800°C for 1.5 hours.
[0011] Preferably, the crystallization reaction includes the following steps: mixing the pretreated fly ash, aluminum source, sodium hydroxide and water in the following molar ratios: n(SiO2) / n(Al2O3) = 2.0, n(Na2O) / n(SiO2) = 1.8, n(H2O) / n(Na2O) = 50, then stirring at 45°C for 2 hours to obtain an initial gel, and then crystallizing at 94°C for 8 hours; The aluminum source is sodium aluminate or aluminum hydroxide.
[0012] The second technical solution of the present invention provides a low-grade high-iron fly ash-based multi-level porous type A molecular sieve prepared according to the above method.
[0013] The third technical solution of the present invention provides an application of the above-mentioned low-grade high-iron fly ash-based multi-level porous type A molecular sieve in the adsorption and purification of CO2 waste gas.
[0014] Preferably, the CO2 volume fraction in the CO2 exhaust gas is 3%.
[0015] The beneficial technical effects of the present invention are as follows: This invention utilizes a unique pretreatment and synthesis process to transform the impurity iron portion of high-iron fly ash into beneficial components, simultaneously constructing a hierarchical porous structure, ultimately producing a molecular sieve adsorbent with excellent adsorption performance for low-concentration CO2. This method achieves a controllable transformation of iron species from their oxide form in the raw material to their framework-doped form (Fe-O-Si) in the final product. This process not only avoids the negative impact of iron on the crystallization process but also makes it an active site for enhancing adsorption performance. Without introducing pore-forming agents, the preparation process defined by this invention allows for the regulation of crystal growth and aggregation behavior, in-situ fabrication of a hierarchical porous structure, and the resulting molecular sieve exhibits high adsorption capacity for low-concentration CO2, making it suitable for CO2 capture in flue gas and possessing significant application value. The preparation method of this invention is simple and convenient, involving only conventional chemical equipment, with low energy consumption and raw material costs, and has the potential for large-scale industrial production. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 The XRD diffraction patterns of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention and the precursor solution in Example 1 are compared.
[0018] Figure 2 The UV-Raman spectra of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention, and the precursor liquid in Example 1.
[0019] Figure 3 The UV-Vis spectra of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention, and the precursor liquid in Example 1.
[0020] Figure 4 The nitrogen adsorption-desorption isotherm and pore size distribution curve of the molecular sieve prepared in Example 1 of this invention are shown. Among them, (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution curve.
[0021] Figure 5 This is a comparison of the adsorption and breakthrough curves of the molecular sieve prepared in Example 1 of the present invention and the commercially available 4A molecular sieve for low concentration CO2.
[0022] Figure 6 The image shows the SEM-mapping of iron in the fly ash pretreatment process of Example 1. Wherein, a represents the original fly ash, b represents calcined fly ash, c represents acid-washed fly ash, and d represents pretreated fly ash.
[0023] Figure 7 These are XPS spectra of samples from each stage of fly ash pretreatment in Example 1 of this invention. Among them, (a) is the original fly ash sample, (b) is calcined fly ash, (c) is acid-washed fly ash, and (d) is pretreated fly ash.
[0024] Figure 8 The XRD pattern is shown for the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention.
[0025] Figure 9 The nitrogen adsorption-desorption isotherm of the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention.
[0026] Figure 10 The pore size distribution curve is shown for the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention. Detailed Implementation
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0028] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0029] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.
[0030] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.
[0031] A method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without template agents includes the following steps: Low-grade high-iron fly ash is calcined, acid-washed and alkali-fused to obtain pretreated fly ash, which is then subjected to a crystallization reaction. The solid product after the reaction is taken out, cleaned and dried to obtain a multi-level porous type A molecular sieve. The low-grade high-iron fly ash has an Fe2O3 mass fraction of 20-40%.
[0032] Furthermore, the calcination temperature is 750°C and the time is 2 hours.
[0033] Furthermore, the acid washing includes the following steps: placing the calcined fly ash in a hydrochloric acid solution with a concentration of 6-7 mol / L and reacting it at 90-95℃ for 5-6 hours.
[0034] Furthermore, the alkali fusion activation includes the following steps: thoroughly mixing and grinding anhydrous sodium carbonate (soda ash) and acid-washed fly ash at a mass ratio of 1.2:1, and then calcining at 800°C for 1.5 hours.
[0035] The stability and assembly of the primary structural units (double four-membered rings) of 4A molecular sieves (LTA type) are highly dependent on the charge balance and space-filling effect provided by sodium ions. The sufficient and uniformly distributed sodium ions (derived from anhydrous sodium carbonate) introduced during the alkali fusion process of this invention play a guiding and stabilizing role similar to an "inorganic template" in the early stages of molecular sieve nucleus formation and growth. This guides silicon and aluminum species to assemble around the nucleus into specific cage-like structures, thereby ensuring the highly selective synthesis of pure-phase type A molecular sieves without the addition of organic template agents, and avoiding the formation of impurity phases.
[0036] Furthermore, the crystallization reaction includes the following steps: The crystallization reaction includes the following steps: The pretreated fly ash, aluminum source, sodium hydroxide and water are mixed according to the following molar ratio: n(SiO2) / n(Al2O3) is 2.0, n(Na2O) / n(SiO2) is 1.8, n(H2O) / n(Na2O) is 50, and then stirred at 45°C for 2 hours to obtain an initial gel, and then crystallized at 94°C for 8 hours; The aluminum source is sodium aluminate or aluminum hydroxide. Crystallization time is crucial to the structure and properties of the product: when the crystallization time is too short (e.g., less than 8 hours), a large amount of highly active aluminosilicate precursors fail to react fully and remain mainly in the form of amorphous gels or intermediates (such as sodium aluminosilicate hydrate). Furthermore, the characteristic peaks of tetracoordinate iron are weak, dd transitions are not obvious, and iron elements mostly exist in non-framework oxide forms, easily clogging the pores. Conversely, if the crystallization time is too long, although it may be beneficial to the stability of tetracoordinate iron species, the continuous alkaline hydrothermal environment can easily lead to excessive crystal growth, destroying the hierarchical porous structure of the molecular sieve. Therefore, controlling the crystallization time to 8 hours is key to achieving effective incorporation of iron species into the framework and forming an ideal hierarchical porous structure.
[0037] This invention uses pretreated fly ash as the main silicon and aluminum source, eliminating the need for additional raw materials such as template agents.
[0038] The core mechanism of this invention is to utilize iron in fly ash as a crystal growth regulator and framework component. For low-iron fly ash (such as 3~8% Fe2O3), after the pretreatment process defined in this invention, the remaining iron content is insufficient to play the same "regulator" role. The structure (such as pore structure and its regularity) and morphology of iron species in the synthesized products will be different, ultimately making it impossible to obtain the hierarchical porous type A molecular sieve of this invention.
[0039] The fly ash raw material used in the following embodiments and comparative examples of this invention is Liupanshui high-iron fly ash. This type of fly ash is a low-grade fly ash with high iron content (Fe2O3 mass fraction 20-40%), abundant inert mullite and quartz mineral phases (20-40%), and low reactivity. However, after being treated by the pretreatment process specified in this invention, it can provide a high-quality silica-alumina source for molecular sieve synthesis. In addition, the high Fe content in this raw material lays the foundation for the subsequent preparation of hierarchical porous type A molecular sieves: after pretreatment, the Fe element will be converted into Fe... 2+ and Fe 3+ The oxide form of Fe atoms is uniformly distributed in the sample and participates in the formation of the framework. Larger Fe atoms replace silicon atoms in the framework, leading to pore expansion and increased size.
[0040] Unless otherwise specified, "room temperature" in this invention refers to 10-30°C.
[0041] All raw materials used in the following embodiments and comparative examples of the present invention are commercially available products.
[0042] Example 1 A method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without template agents, comprising the following steps: (1) Calcination: The fly ash raw material (the mass percentage of its main components is shown in Table 1) was passed through a 200-mesh sieve as a test sample. The sieved fly ash was calcined at high temperature in a muffle furnace (750℃, held for 2 hours), then removed and cooled to room temperature to obtain calcined fly ash, which was stored for later use. This step is used to remove residual carbon and some volatile substances from the fly ash and to preliminarily activate it.
[0043] (2) Acid washing: Calcined fly ash is reacted with a 6 mol / L hydrochloric acid aqueous solution at 94°C for 5 hours, then the solid and liquid are separated, and the fly ash is washed with deionized water until neutral to obtain acid-washed fly ash. This step aims to selectively dissolve impurity elements such as calcium, magnesium and some iron, significantly reduce the impurity content, and relatively enrich silicon and aluminum.
[0044] (3) Alkali fusion activation: Anhydrous sodium carbonate (soda ash) and acid-washed fly ash are thoroughly mixed and ground at an alkali-to-ash mass ratio of 1.2:1. The mixture is then calcined at 800℃ for 1.5 hours to obtain pretreated fly ash (the mass percentage of the main components is shown in Table 1). This process is used to convert the inert mullite, quartz and other crystalline phases and amorphous glass phases in fly ash into soluble active aluminosilicates such as sodium metasilicate and nepheline, providing highly reactive silicon and aluminum sources for subsequent hydrothermal synthesis.
[0045] Table 1 Table 1 shows that the pretreatment steps defined in this invention effectively removed most of the Fe impurities from the fly ash. However, because some iron was encapsulated within the fly ash's internal structure and chemically bonded to inert aluminosilicates, it was difficult to achieve sufficient contact with hydrochloric acid during acid leaching, thus failing to completely remove it. During the subsequent alkali fusion activation process, the amorphous aluminosilicate phase of the fly ash was destroyed, releasing the encapsulated iron elements, which then existed in a uniformly dispersed state within the activation product. This residual iron oxide, acting as an active iron source, provides a crucial material basis for iron doping into the molecular sieve framework and forming a hierarchical porous structure during subsequent hydrothermal crystallization.
[0046] (4) The pretreated fly ash obtained in step (3) is used as the main silicon source and aluminum source. XRF characterization test is performed. The amount of raw materials added, such as pretreated fly ash, aluminum source (sodium aluminate), sodium hydroxide (alkali source) and deionized water, is controlled according to the test results. The corresponding amount of raw materials is added to make the molar ratio of n(SiO2) / n(Al2O3) 2.0, n(Na2O) / n(SiO2) 1.8 and n(H2O) / n(Na2O) 50 in the sample. The mixture is stirred continuously at 45°C for 2 hours to form a uniform initial gel.
[0047] (5) Transfer the uniform gel obtained in step (4) to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner to obtain a precursor solution (denoted as 4A-0), and seal it. Place the reactor in a constant temperature oven and carry out a crystallization reaction at 94°C for 8 hours.
[0048] (6) After the crystallization reaction is completed, the reaction vessel is naturally cooled to room temperature, the reaction product is taken out, and solid-liquid separation is performed. The solid product is repeatedly washed with deionized water until the pH value of the filtrate is neutral. The washed solid is dried at 100°C for 6 hours to obtain high-iron fly ash based multi-level porous type A molecular sieve (denoted as 4A-8).
[0049] Figure 4The nitrogen adsorption-desorption isotherm and pore size distribution curve of the molecular sieve prepared in Example 1 of this invention are shown. Among them, (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution curve.
[0050] The pore types, corresponding pore volumes, and their proportions in the molecular sieve prepared in Example 1 are shown in Table 2.
[0051] Table 2 Depend on Figure 4 It can be seen that the pore size of the high-iron fly ash-based hierarchical porous type A molecular sieve prepared in Example 1 is mainly distributed at 5.01 nm. The proportion of pores with a pore size > 50 nm is 7.47%. The specific surface area of the prepared high-iron fly ash-based hierarchical porous type A molecular sieve is 44.763 m². 2 / g, external surface area is 69.047m² 2 / g, total pore volume is 0.112cm³ 3 / g.
[0052] Comparative Example 1 According to the research of Li et al. [Synthesizing molecular sieves from kaolin and fly ash at China University of Geosciences], this study synthesized type A molecular sieves with an average pore size of 5.29 nm using kaolin (SiO2 content of 37.57%, Al2O3 content of 34.73%, and Fe2O3 content of 3.22%), which has similar main components to fly ash, without acid leaching to remove impurities or using a template agent.
[0053] Comparative Example 2 The only difference from Example 1 is that the crystallization reaction time in step (5) was changed from 8 hours to 0.5h, 1.5h, 2h, 4h, and 6h, respectively. The products obtained were denoted as 4A-0.5, 4A-1.5, 4A-2, 4A-4, and 4A-6, respectively.
[0054] Comparative Example 3 The only difference in Example 1 is that the fly ash raw material in step (1) is replaced with low-iron fly ash to prepare a low-iron fly ash-based molecular sieve. The mass percentage of the main components of the low-iron fly ash is shown in Table 3.
[0055] Table 3 Figure 8 The XRD pattern is shown for the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention.
[0056] Figure 9 The nitrogen adsorption-desorption isotherm of the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention.
[0057] Figure 10The pore size distribution curve is shown for the low-iron fly ash-based molecular sieve prepared in Comparative Example 3 of this invention.
[0058] Effect verification The XRD diffraction patterns of the molecular sieves prepared in Example 1 and Comparative Example 2, as well as the precursor solution of Example 1 before crystallization, were tested respectively. The test results are as follows: Figure 1 As shown.
[0059] Figure 1 The XRD diffraction patterns of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention and the precursor solution in Example 1 are compared.
[0060] Figure 2 The UV-Raman spectra of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention, and the precursor liquid in Example 1.
[0061] Figure 3 The UV-Vis spectra of the molecular sieves prepared in Example 1 and Comparative Example 2 of this invention, and the precursor liquid in Example 1.
[0062] The pickling process significantly reduces the total iron content (from 32.3% to 11.3%), avoiding interference from excessive iron in subsequent crystallization; the remaining iron after pickling is the key active iron source for subsequent steps. (See UV-Raman spectrum). Figure 2 ) and UV-vis spectrum ( Figure 3 As shown in the figure, the residual iron ions in the pretreated fly ash participate in the formation of the molecular sieve framework (forming Fe-O-Si bonds), playing a role in self-templating and crystal growth regulation, ultimately resulting in the formation of a hierarchical porous structure in the molecular sieve.
[0063] In the initial stage of the crystallization reaction, iron species are distributed in a highly uniform manner throughout the reaction system. At this time, aluminosilicate species undergo condensation and polymerization first, initially constructing an ordered molecular sieve pore framework. In the middle stage of crystallization, these highly dispersed iron species begin to enter and integrate into the growing primary silica-alumina framework. In the later stage of crystallization, as the directional order of the molecular sieve framework structure reaches a high level, iron species are stably embedded in the finally formed molecular sieve framework, ultimately transforming into iron-active species at the framework sites through the formation of stable Fe-O bonds.
[0064] Compared with commercially available 4A molecular sieves (purchased from Gongyi Hengxin Materials Co., Ltd., the commercially available 4A molecular sieve used has uniform micropores with an average pore size of 0.42 nm, which is standard for type A molecular sieves, and a BET specific surface area of 950 m²), the 4A molecular sieve used has uniform micropores. 2 / g。) Low-concentration CO2 adsorption tests were conducted. The specific test method was as follows: Gas chromatography was used to evaluate the adsorption performance of the molecular sieve sample in low-concentration CO2 gas (CO2 volume fraction 3%, N2 volume fraction 97%). 0.75g of molecular sieve sample was weighed, pressed into tablets, ground to 40-60 mesh, and pretreated by high-temperature desorption at 450℃ for 5h in a muffle furnace. The tablets were then placed in a fixed-bed reactor, with the total flow rate of the mixed gas set at 10mL / min and the adsorption temperature set at 25℃. Gas chromatography was used to detect the CO2 concentrations at the inlet and outlet.
[0065] A comparison of the adsorption breakthrough curves of the molecular sieve prepared in Example 1 and the commercially available 4A molecular sieve for low concentrations of CO2 under the same conditions is shown below. Figure 5 As shown in the figure. The test results are shown in Table 4.
[0066] Table 4 Because the macropores in the product of Example 1 of this invention provide macroscopic diffusion channels with less resistance for gas molecules, during dynamic adsorption, the CO2-containing feed gas can rapidly and without retention penetrate deep into the adsorbent particles, avoiding the formation of a concentration boundary layer on the outer surface of the particles, thereby shortening the initial adsorption breakthrough time. The hierarchical pore structure of this invention increases the diffusion resistance from the micropore scale to the mesopore / macropore scale, accelerating the gas diffusion rate and thus improving the overall adsorption kinetics performance and adsorption efficiency.
[0067] Figure 6 The image shows the SEM-mapping of iron in the fly ash pretreatment process of Example 1. Wherein, a represents the original fly ash, b represents calcined fly ash, c represents acid-washed fly ash, and d represents pretreated fly ash.
[0068] Iron in fly ash raw materials does not exist in a single, uniform form, but rather in a complex, multi-form mixture. This complexity is the fundamental reason for the existence of the pretreatment process (calcination, acid washing, and alkali fusion activation) in this invention, and it is also the premise for this invention to transform "impurity iron" into "functional iron." The iron in fly ash mainly exists in three forms: the first is independently existing iron oxides (such as magnetite Fe3O4 and hematite Fe2O3). This type of iron has high chemical activity and readily reacts with acid, making it the main target for removal in the acid leaching step. If this type of iron is not removed, it easily forms large particles of inert impurities during the crystallization reaction, severely hindering the nucleation and growth of molecular sieves, or clogging the pores. (SEM-mapping image) Figure 6 As shown in a) and b), a small portion of Fe elements have an independent enriched phase in the original fly ash sample, which is consistent with the morphology of "iron oxides" described in the text.
[0069] The other two types are iron ions dissolved in the crystalline phase (such as mullite), and iron oxides or ions encapsulated in amorphous silica-alumina glass. Due to their stable chemical environment, these two forms of iron are difficult to completely remove by conventional acid leaching (the Fe2O3 content can still reach 11.3% after acid leaching). However, subsequent alkali fusion treatment can completely destroy the mullite structure and glassy phase, allowing the encapsulated or fixed iron, along with silicon, aluminum, sodium, and other elements, to transform into highly reactive species, providing an ideal and uniform precursor for the subsequent hydrothermal synthesis of iron-containing molecular sieves.
[0070] To further investigate the changes in Fe-O chemical bonds in fly ash raw materials during pretreatment, XPS was used to characterize and analyze the valence state changes of iron during fly ash pretreatment. Figure 7 As shown in the figure. The XPS peak fitting results are shown in Table 5.
[0071] Figure 7 These are XPS spectra of samples from each stage of fly ash pretreatment in Example 1 of this invention. Among them, (a) is the original fly ash sample, (b) is calcined fly ash, (c) is acid-washed fly ash, and (d) is pretreated fly ash.
[0072] Table 5 Table 5 shows that the Fe values fitted from the original fly ash sample... 2+ / Fe 3+ The area ratio was 0.58, indicating that the Fe in the original fly ash sample was relatively low. 2+ More than Fe 3+ However, after high-temperature calcination, some Fe... 2+ Oxidized to Fe 3+ The performance is characterized by the fitted Fe 2+ / Fe 3+ The area ratio decreased from 0.58 to 0.40. Fe after acid leaching of fly ash 2+ / Fe 3+ The area ratio decreased to 0.09, indicating that acid leaching treatment can reduce the Fe content in calcined fly ash. 2+ The Fe content decreased significantly, and this phenomenon was consistent with the XRF results of the pretreatment process; the Fe content of the pretreated fly ash after alkali fusion activation was significantly reduced. 2+ / Fe 3+ The area ratio increased from 0.09 to 0.24, mainly because the alkali-activated fly ash can release some of the iron present in amorphous aluminosilicates.
[0073] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing low-grade high-iron fly ash-based hierarchical porous type A molecular sieves without template agent for CO2 waste gas adsorption and purification, characterized in that, Includes the following steps: Low-grade high-iron fly ash is calcined, acid-washed, and activated by alkali fusion to obtain pretreated fly ash, which is then subjected to a crystallization reaction to complete the preparation. The low-grade high-iron fly ash has an Fe2O3 mass fraction of 20-40%; The crystallization reaction includes the following steps: mixing the pretreated fly ash, aluminum source, sodium hydroxide and water in the following molar ratios: n(SiO2) / n(Al2O3) = 2.0, n(Na2O) / n(SiO2) = 1.8, n(H2O) / n(Na2O) = 50, then stirring at 45°C for 2 hours to obtain an initial gel, and then crystallizing at 94°C for 8 hours; The aluminum source is sodium aluminate or aluminum hydroxide; The pickling solution is a hydrochloric acid aqueous solution with a concentration of 6-7 mol / L; The pickling temperature is 90~95℃, and the time is 5-6 hours; The hierarchical pore structure increases the diffusion resistance from the micropore scale to the mesopore and macropore scale, thereby accelerating the gas diffusion rate and improving the overall adsorption kinetics performance, resulting in higher adsorption efficiency.
2. The method according to claim 1, characterized in that, The calcination temperature was 750℃ and the time was 2 hours.
3. The method according to claim 1, characterized in that, The alkaline fusion activation includes the following steps: mixing sodium carbonate and acid-washed fly ash at a mass ratio of 1.2:1, and then calcining at 800°C for 1.5 hours.
4. A low-grade high-iron fly ash-based multi-level porous type A molecular sieve prepared by the method according to any one of claims 1-3.
5. The application of the low-grade high-iron fly ash-based multi-level porous type A molecular sieve as described in claim 4 in the adsorption and purification of CO2 waste gas.
Citation Information
Patent Citations
Method for synthesizing different carbon dioxide adsorbents from building clay bricks
CN115318242A